Light-Emitting Electrochemical Cells : Concepts, Advances and Challenges - Costa, Rubén D. (Springer International Publishing : Imprint: Springer, 2017)
This book presents the recent achievements towards the next generation of Light-emitting electrochemical cells (LEC). Its first part focus on the definition, history and mechanism of LEC, going then to concepts and challenges and, finally, giving the reader examples of current application of new electroluminescent materials. The chapters are written by different international groups working on LEC.